Validitas Pengembangan Modul Ajar IPA Berbasis PjBL Bermuatan Ethno-STEAM untuk Memberdayakan Kemampuan Berpikir Kreatif Pada Materi Ekologi dan Keanekaragaman Hayati di Indonesia - Melynia Ariningtyas Prabawati; Sri Yamtinah; Bramastia Bramastia (Postgraduate, University of Mataram, 2025)
Biodiversity in Indonesia is a science material that is closely related to environmental conditions, daily life events, and natural characteristics in Indonesia. Ethno-STEAM content is a local wisdom-based learning approach that connects theory and skills in the fields of Science, Technology, Engineering, Arts, and Mathematics. Mastery of material for junior high school students is expected to be able to apply their knowledge to the environment through STEAM, be able to solve problems, become logical thinkers, and be able to link culture and local wisdom with learning. This study aims to describe the validity of teaching modules in science learning to empower students' creative thinking skills at the junior high school level. The development of PjBL-based science teaching modules with Ethno-STEAM content uses the 4D model development research approach. The validity in this study includes the validity of the material with an acquisition of 0.98, media experts of 0.95, learning experts of 0.90 and language of 0.95, the four validations have been validated by 7 expert and practical validators and are included in the very valid category. The validity of the Ethno-STEAM-loaded test instrument using a written test and analyzed using Aiken's validity which has been adjusted to the creative thinking indicators obtained an average validity test of 0.94. It is concluded that the science teaching module is suitable for use as a PjBL-based learning media and ethno-STEAM content to empower students' creative thinking skills